2015
DOI: 10.4081/ijas.2015.3464
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterisation ofκ–CaseinGene inGirgentanaDairy Goat Breed and Identification of Two New Alleles

Abstract: The k-casein fraction plays an important role in the formation, stabilisation and aggregation on casein micelles and thus affects technological and nutritional properties of milk. In this study, exon 4 of k-casein (CSN3) gene was sequenced and analysed in Girgentana goat breed. Analyses of the obtained sequences showed the presence of A, B, D, and G known alleles and two new genetic variants, named D' and N. The new D' allele differs from D in one transition, G284→A284, which did not cause amino acid change. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 24 publications
2
16
1
Order By: Relevance
“…In a previous study Gigli et al (2008) reported A-C-A-B as the most frequent in Girgentana goat. These results may be explained considering the different allele frequency at CSN3*A reported by Di Gerlando et al (2015) (0.480) compared with those reported in the previous study by Gigli et al (2008) (0.127). In fact, the flocks are not the same of Gigli et al (2008) and number of animals within flocks has changed during these past years, and then, the individual analysed samples are not the same of previous work.…”
Section: Casein Haplotypescontrasting
confidence: 52%
See 2 more Smart Citations
“…In a previous study Gigli et al (2008) reported A-C-A-B as the most frequent in Girgentana goat. These results may be explained considering the different allele frequency at CSN3*A reported by Di Gerlando et al (2015) (0.480) compared with those reported in the previous study by Gigli et al (2008) (0.127). In fact, the flocks are not the same of Gigli et al (2008) and number of animals within flocks has changed during these past years, and then, the individual analysed samples are not the same of previous work.…”
Section: Casein Haplotypescontrasting
confidence: 52%
“…Molecular data of casein (CAS) gene polymorphisms for Girgentana breed from our previous studies on CSN1S1 (Mastrangelo et al 2013a), CSN2 (Tortorici et al 2014), CSN1S2 (Palmeri et al 2014), and CSN3 (Di Gerlando et al 2015), were used to infer haplotypes. Haplotypes distributions were analysed using HAPLOTYPE procedures of SAS (SAS Institute Inc.).…”
Section: Casein Haplotypesmentioning
confidence: 99%
See 1 more Smart Citation
“…e For computation of the number of theoretical plates, peak width at the baseline was obtained by tangential lines drawn at half-height. However, the casein genetic variants quantified in our study were the most frequent in Girgentana goat breed; in fact, at CSN1S2, the most frequent alleles were A and F (Palmeri, Mastrangelo, Sardina, & Portolano, 2014), at CSN2 were C and C1 (Tortorici, Di Gerlando, Mastrangelo, Sardina, & Portolano, 2014), and at CSN3 gene were A and B (Di Gerlando et al, 2015). Comparing our data with those reported by Bonanno et al (2013), which used a different chromatographic method, it can be possible to state that our applied chromatographic conditions allowed in less time running, run was 5 min shorter, a greater separation and resolution of caseins as higher distance between caseins peaks.…”
Section: Separationmentioning
confidence: 99%
“…Tortorici et al (2014) showed the presence of C, C1 and A strong alleles, and 0' null allele at CSN2 gene, whereas the most common genotypes are CC1 followed by CC, C1C1 and C0′. The exon 4 of CSN3 gene was sequenced and analysed by Di Gerlando et al (2015). Analyses of the obtained sequences showed the presence of A, B, D and G known alleles and two new genetic variants, named D′ and N. The most common genotype is AB followed by AA, AD and BB.…”
Section: Casein Genesmentioning
confidence: 99%